(untitled) (Carte Romanze, 2022)
The article offers a study of the fifteenth century ms. Parma, Biblioteca Palatina, 25 (Pr), a new witness of the Fatti di Cesare (versione breve) never reported before. The presentation of the different sections of the codex, with particular attention to the legend of St. Jerome, is followed by a detailed analysis of the text of the Fatti di Cesare, as well as by a classification of Pr within its manuscript tradition.